Program pendampingan pembuatan SPP-IRT bagi para pelaku UMKM guna meningkatkan market pemasaran produk di Desa Gogodalem Kabupaten Semarang - Wulandari, Ikhlima; Isnaosa, Dwi Mey; Arsyika, Bilqis Azillanii Tahta; Pamungkas, Metta Ramadhani; Mustofa, Nur Huri (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
The assistance program for obtaining the Home Industry Food Production Certificate (SPP-IRT) was aimed at Micro, Small, and Medium Enterprises (MSMEs) to expand their product marketing in Gogodalem Village, Semarang Regency. This community service activity sought to develop the Village's potential, mainly through its natural resources. Data collection methods included observation, interviews, identifying gaps in compliance with Good Manufacturing Practices (CPPB-IRT), preparing required documents, and registering for the SPP-IRT. Observations and interviews were conducted with the Gulakacang and Dapur Cantika MSMEs. The interview with Gulakacang revealed that they required assistance in renewing their SPP-IRT. Meanwhile, Dapur Cantika needed support to issue a new SPP-IRT. Dapur Cantika successfully obtained their P-IRT certificates, with P-IRT number 6053322020821-29 for Chocolate Nastar Cake and P-IRT number 6053322010821-29 for Pineapple Nastar Cake. Meanwhile, the P-IRT for Gulakacang was directly provided by the Health Department on March 1, 2029, during an on-site visit, with P-IRT number 2113322010843-29.